COMMUNICATION CULTURE OF SANGIRAN WORLD HERITAGE SITE SOCIETY: AN ETHNOGRAPHY STUDY - Arofah, Kurnia; Suparno, Basuki Agus (PEOPLE: International Journal of Social Sciences, 2019)
Sangiran site in Indonesia, is one of world conservation sites listed by Unesco in 1996 in which many scholars and students give an attention to study the human evolution there, or tourists come to get a unique experience in archeological site. Problem arise when the development of the site expected by residents, contradict over the conservation principle of an archaeological site. Current solutions on the site’s conservation become grievance by the residents who feel that the conservation only concerns to fossils and sites, yet neglecting the existence of resident who has been living for long time in Sangiran area. This research use ethnography of communication methods to explore how communication culture in Sangiran site affecting the conservation effort. Result from the research shows: 1. There are two main themes of messages as narration that was shared an inside and an outside among group or community in Sangiran site. First narration was talking about Mythology vs Science perception related to Sangiran Site existence. Second, theme that was related to Economy vs Conservation perception in Sangiran; 2. There are communication gap activity between Sangiran residents and some institutions that involved and interested in Sangiran and vice-versa. Therefore, prejudice, rumors and issues emerge between both sides hinder the spirit of conservation of site for the prosperity for all party related to Sangiran. In a nutshell, communication forum such as focus group discussion or public hearing needed to unite all party in Sangiran so the communication gap could be bridged.